Status of Paddy Straw Management Technologies in Punjab - Kaur, Amanjot; Kaur , Prabhjot; Kumar , Pankaj (Indian Journal of Extension Education, 2021)
Maximum straw burning was practiced in south-western districts of Punjab; Bathinda is the one of them which was selected for the study. Study was conducted to know about awareness and status of paddy straw management technologies in Bathinda district. For this study, 135 respondents were selected from Bathinda district randomly. Result showed that all the respondents were aware about the happy seeder, super straw management system and baler. No respondents had awareness regarding paddy straw management techniques like cutter-cum spreader, packaging fruits and vegetables etc. So it was essential to create awareness programs for them. Majority of respondents adopted happy seeder and super straw management system. However, from past few years area under these technologies was decreased and area under baler, mulcher and chopper-cum-spreader was increased. Respondents realized that use of baler was highly complex so usage of baler needs to be made simple. Adoption of happy seeder marked some different type of agronomic practices such as difficulty in sowing operation, increase in pesticide spray requirement, decrease irrigation requirement and many more.
Keywords: Adoption; Agronomic practices; Awareness; Management technologies; Paddy straw